2018
DOI: 10.1101/464388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In for a penny, in for a pound: Examining motivated memory through the lens of retrieved context models

Abstract: When people encounter items that they believe will help them gain reward, they later remember them better than those that do not. While it is adaptive to preferentially remember experiences that will be useful later, it is unknown how the competition for memory resources is implemented in time, through the processes of encoding, consolidation, and retrieval. In two experiments we promised participants £1 for remembering some pictures, but only 10 pence for remembering others. Their ability to describe the pict… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 92 publications
(174 reference statements)
2
3
0
Order By: Relevance
“…Reward-enhanced memory was dependent on list context, meaning that recall of items that predicted reward was increased in mixed lists, but not in pure lists, replicating a recent study from our group (Talmi et al, 2021). The finding that reward did not enhance recall in pure lists places an important constraint on any explanation of reward-enhanced memory as solely a function of automatic encoding processes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Reward-enhanced memory was dependent on list context, meaning that recall of items that predicted reward was increased in mixed lists, but not in pure lists, replicating a recent study from our group (Talmi et al, 2021). The finding that reward did not enhance recall in pure lists places an important constraint on any explanation of reward-enhanced memory as solely a function of automatic encoding processes.…”
Section: Discussionsupporting
confidence: 83%
“…Findings from the mixed list condition agreed with the recall dynamics that this computational model predicted. In agreement with the prediction that the high reward items are more tightly bound to the encoding context and therefore will be more likely to be recalled first (Talmi, Lohnas, et al, 2019; Talmi et al, 2021), participants recalled high-reward items earlier than low-reward items. While in previous studies of recall of mixed lists of ‘strong’ and ‘weak’ items the propensity to recall ‘stronger’ items early was confounded with the increased average recall of such items, here we observed that high-reward items were recalled earlier than low-reward items while controlling for this confound.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Given that emotional salience modulates episodic memory, it follows that it should also modulate action evaluation in TCM-SR. We examine this issue below. For present purposes, we gloss over the many differences between emotional stimuli, prioritized stimuli, and rewards and punishments with varied magnitude, referring to all of them as 'emotionally salient' or 'important' states, and speak generally about 'emotional modulation' to refer to their effect on memory (Talmi, Kavaliauskaite, & Daw, 2018).…”
Section: Emotional Modulation Of Memory Yields Bias-variance Trade-offmentioning
confidence: 99%